Weight-adjusted lean body mass and calf circumference are protective against obesity-associated insulin resistance and metabolic abnormalities. Issue 7 (July 2017) - Takamura, Toshinari; Kita, Yuki; Nakagen, Masatoshi; Sakurai, Masaru; Isobe, Yuki; Takeshita, Yumie; Kawai, Kohzo; Urabe, Takeshi; Kaneko, Shuichi
Abstract: Background: To test the hypothesis that preserved muscle mass is protective against obesity-associated insulin resistance and metabolic abnormalities, we analyzed the relationship of lean body mass and computed tomography-assessed sectional areas of specific skeletal muscles with insulin resistance and metabolic abnormalities in a healthy cohort. Methods: A total of 195 subjects without diabetes who had completed a medical examination were included in this study. Various anthropometric indices such as circumferences of the arm, waist, hip, thigh, and calf were measured. Body composition (fat and lean body mass) was determined by bioelectrical impedance analysis. Sectional areas of specific skeletal muscles (iliopsoas, erector spinae, gluteus, femoris, and rectus abdominis muscles) were measured using computed tomography. Findings: Fat and lean body mass were significantly correlated with metabolic abnormalities and insulin resistance indices. When adjusted by weight, relationships of fat and lean body mass with metabolic parameters were mirror images of each other. The weight-adjusted lean body mass negatively correlated with systolic and diastolic blood pressures; fasting plasma glucose, HbA1c, alanine aminotransferase, and triglyceride, and insulin levels; and hepatic insulin resistance indices, and positively correlated with HDL-cholesterol levels and muscle insulin sensitivity indices. Compared with weight-adjusted lean body mass, weight-adjusted sectional areas of specific skeletal muscles showed similar, but not as strong, correlations with metabolic parameters. Among anthropometric measures, the calf circumference best reflected lean body mass, and weight-adjusted calf circumference negatively correlated with metabolic abnormalities and insulin resistance indices. Interpretation: Weight-adjusted lean body mass and skeletal muscle area are protective against weight-associated insulin resistance and metabolic abnormalities. The calf circumference reflects lean body mass and may be useful as a protective marker against obesity-associated metabolic abnormalities.